Study of Demographic Characteristics vis-à-vis Social Status of Households: Exploring the Relationship Between Demographic Characteristics and Social Status in Households (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Demographic characteristics describe the total development fabric of society in terms of its religious composition ,male-female composition, distribution, density, age and sex composition , size of family, marital status, births and deaths etc. These are all important aspects of population which indicate in which direction the human resource are heading are helpful in determining further course of development while planning.